Association of beta-blockers beyond 1 year after myocardial infarction and cardiovascular outcomes - Ishak, Divan; Aktaa, Suleman; Lindhagen, Lars; Alfredsson, Joakim; Dondo, Tatendashe Bernadette; Held, Claes; Jernberg, Tomas; Yndigegn, Troels; Gale, Chris P; Batra, Gorav (Heart (British Cardiac Society), 2023)
ObjectiveBeta-blockers (BB) are an established treatment following myocardial infarction (MI). However, there is uncertainty as to whether BB beyond the first year of MI have a role in patients without heart failure or left ventricular systolic dysfunction (LVSD).MethodsA nationwide cohort study was conducted including 43 618 patients with MI between 2005 and 2016 in the Swedish register for coronary heart disease. Follow-up started 1 year after hospitalisation (index date). Patients with heart failure or LVSD up until the index date were excluded. Patients were allocated into two groups according to BB treatment. Primary outcome was a composite of all-cause mortality, MI, unscheduled revascularisation and hospitalisation for heart failure. Outcomes were analysed using Cox and Fine–Grey regression models after inverse propensity score weighting.ResultsOverall, 34 253 (78.5%) patients received BB and 9365 (21.5%) did not at the index date 1 year following MI. The median age was 64 years and 25.5% were female. In the intention-to-treat analysis, the unadjusted rate of primary outcome was lower among patients who received versus not received BB (3.8 vs 4.9 events/100 person-years) (HR 0.76; 95% CI 0.73 to 1.04). Following inverse propensity score weighting and multivariable adjustment, the risk of the primary outcome was not different according to BB treatment (HR 0.99; 95% CI 0.93 to 1.04). Similar findings were observed when censoring for BB discontinuation or treatment switch during follow-up.ConclusionEvidence from this nationwide cohort study suggests that BB treatment beyond 1 year of MI for patients without heart failure or LVSD was not associated with improved cardiovascular outcomes.